PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA - Sinaga, D. Yuliana; Sidabutar, Ropinus (Unversitas Katolik Santo Thomas, 2022)
This study aims to improve students' mathematics learning outcomes with the Learning Based Learning Model in the 2013 T.A 2021/2022 Curriculum. This research is a classroom action research conducted in two cycles. Each cycle consists of 4 stages, namely: planning, implementation, observation, and reflection. The subjects of this study were fourth grade students, totaling 35 people consisting of 15 males and 20 females. The object of research is the result of students' mathematics learning. Data were analyzed using descriptive statistics. The results showed that the Problem Based Learning learning model can improve the mathematics learning outcomes of fourth grade students in the 2013 Curriculum. This is known from the pre-cycle student learning outcomes with an average score of 60.50 and learning completeness of 42.85% in the low category. In the first cycle, the results experienced an average value of 68.85 and 51.42% learning completeness which was in the sufficient category. The research was continued in the second cycle and obtained an average score of 80.35 and a learning completeness of 82.85% which was in the high category and had met the criteria for indicators of research success. So, it can be concluded that the application of the Problem Based Learning learning model can improve students' mathematics learning outcomes.